1979
DOI: 10.1038/ki.1979.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metabolic acidosis and alkalosis on sodium and calcium transport in the dog kidney

Abstract: Clearance and micropuncture studies have been performed in dogs to examine the effects of acute and chronic metabolic acidosis and acute alkalosis on tubular sodium and calcium transport. Acute metabolic acidosis, induced by the infusion of hydrochloric acid, decreased proximal fluid reabsorption and increased the fractional delivery of sodium and calcium to the distal tubule, but not to the final urine. In comparison with normal dogs, dogs with chronic metabolic acidosis (induced by feeding ammonium chloride)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
2
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(121 citation statements)
references
References 20 publications
6
112
2
1
Order By: Relevance
“…Metabolic alkalosis enhances calcium reabsorption. Even when a bicarbonate infusion produces metabolic alkalosis and concomitant volume expansion, a setting in which increased distal sodium delivery would be expected to enhance calcium excretion, increased delivery of bicarbonate to the distal nephron has been shown to increase calcium reabsorption (51). However, metabolic alkalosis is seen much more often in association with volume depletion and chloride losses such as with vomiting.…”
Section: Kidneymentioning
confidence: 87%
See 3 more Smart Citations
“…Metabolic alkalosis enhances calcium reabsorption. Even when a bicarbonate infusion produces metabolic alkalosis and concomitant volume expansion, a setting in which increased distal sodium delivery would be expected to enhance calcium excretion, increased delivery of bicarbonate to the distal nephron has been shown to increase calcium reabsorption (51). However, metabolic alkalosis is seen much more often in association with volume depletion and chloride losses such as with vomiting.…”
Section: Kidneymentioning
confidence: 87%
“…Thiazide diuretics have been reported to be bone sparing (63,115,116) and may reduce the rate of hip fractures and bone loss in postmenopausal osteoporosis (117)(118)(119). This result has been attributed to their widely known effect as an enhancer of renal tubular reabsorption of calcium, but thiazide diuretics also induce metabolic alkalosis, which independently enhances the reabsorption of calcium and also may prevent bone loss (51,52).…”
Section: Bonementioning
confidence: 91%
See 2 more Smart Citations
“…Increased acid load in conditions such as high dietary protein intake and metabolic acidosis increases urinary Ca 2ϩ excretion (92). A recent study reported that extracellular protons bind to a titratable amino acid, glutamate-522 (a "pH sensor"), in the extracellular loop of rabbit TRPV5 and inhibit its activity (93).…”
Section: Role Of Trp In Divalent Ion Homeostasismentioning
confidence: 99%